2014
DOI: 10.1371/journal.pone.0097400
|View full text |Cite|
|
Sign up to set email alerts
|

Trends in Inequalities in Health, Risk and Preventive Behaviour among the Advanced-Age Population in Austria: 1983-2007

Abstract: BackgroundAlthough a number of previous research studies have focused on the long-term analysis of the health and health behaviour of the elderly, there is still a shortage of information in relation to the long-term trends regarding health or risk and preventive behaviour in the elderly population taking into account gender differences and differences in educational level.MethodsThe database comprised subsamples of the Austrian Micro-Census, including individuals aged 65 years and older, for the years 1983, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(28 reference statements)
0
1
0
1
Order By: Relevance
“…In aktuelleren Arbeiten mit österreichischen Daten ist das Gesundheitsverhalten eindimensional oder enumerativ thematisiert worden (Burkert et al 2012;Klimont 2016;Muckenhuber et al 2014Muckenhuber et al , 2015Walther et al 2014;Brunner-Ziegler et al 2013), während multiple Betrachtungen weitgehend fehlen (Dorner et al 2013). Ziel dieses Beitrages ist es, das Gesundheitsverhalten am Beispiel der Wiener Bevölkerung multidimensional zu betrachten.…”
Section: Introductionunclassified
“…In aktuelleren Arbeiten mit österreichischen Daten ist das Gesundheitsverhalten eindimensional oder enumerativ thematisiert worden (Burkert et al 2012;Klimont 2016;Muckenhuber et al 2014Muckenhuber et al , 2015Walther et al 2014;Brunner-Ziegler et al 2013), während multiple Betrachtungen weitgehend fehlen (Dorner et al 2013). Ziel dieses Beitrages ist es, das Gesundheitsverhalten am Beispiel der Wiener Bevölkerung multidimensional zu betrachten.…”
Section: Introductionunclassified
“…The higher level of education of a person is expected to be better health behavior. This was studied by Muckenhuber et al (2014) in Austria in the elderly more than 65 years old using baseline data from micro census in the country which obtained the result that the elderly with higher education had significantly better self-health. A study by Li et al (2014) found that education (bachelor level or higher) is one of the variables that influence the management of personal health in the elderly.…”
Section: Introductionmentioning
confidence: 99%